2009
DOI: 10.1007/s00467-009-1199-5
|View full text |Cite
|
Sign up to set email alerts
|

Tipping the redox balance of oxidative stress in fibrogenic pathways in chronic kidney disease

Abstract: Patients with moderate to advanced chronic kidney disease or end-stage renal disease have a greatly increased cardiovascular risk that cannot be explained entirely by traditional cardiovascular risk factors. An increase in oxidative stress and inflammation have been proposed as nontraditional cardiovascular risk factors in this patient population. Oxidative stress reflects the redox balance between oxidant generation and antioxidant mechanisms. The generation of reactive oxygen species is not simply a random p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 126 publications
(101 reference statements)
0
43
1
1
Order By: Relevance
“…There is a substantial body of evidence supporting the hypothesis that increased oxidative stress plays an important role in the development of fibrotic diseases in humans. 5,32,33 Prior studies centered on the reduction of oxidized macromolecules as the critical component to limiting disease progression, 34,35 rather than the specific redoxsensitive pathways or target cells that are directly modulated by antioxidants. 36,37 We found that cysteamine bitartrate treatment resulted in a substantial reduction in protein oxidation (.50%) despite no change in total thiol levels at advanced time points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a substantial body of evidence supporting the hypothesis that increased oxidative stress plays an important role in the development of fibrotic diseases in humans. 5,32,33 Prior studies centered on the reduction of oxidized macromolecules as the critical component to limiting disease progression, 34,35 rather than the specific redoxsensitive pathways or target cells that are directly modulated by antioxidants. 36,37 We found that cysteamine bitartrate treatment resulted in a substantial reduction in protein oxidation (.50%) despite no change in total thiol levels at advanced time points.…”
Section: Discussionmentioning
confidence: 99%
“…Thiol groups react with almost all physiologic oxidants and can reduce them before they trigger harmful reactions. 5 Chronic kidney injury depletes endogenous intracellular and extracellular antioxidant systems, resulting in increased tissue oxidative stress. [6][7][8] Cysteamine bitartrate is a simple yet interesting aminothiol that is approved by the US Food and Drug Administration for the treatment of patients with cystinosis.…”
mentioning
confidence: 99%
“…Moreover, the available data are limited to information that is routinely collected in the database at 6-months intervals, not allowing for more complete or detailed information. Most importantly, it did not allow for the assessment of an association between chronic inflammatory state or degree of proteinuria and risk of disease progression, both areas of significant interest of late (19).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays an important role in the development of fibrosis. It has been reported that increased oxidative stress plays an important role in the development of fibrotic diseases including idiopathic pulmonary fibrosis (IPF), cystic fibrosis (CF), liver fibrosis/ cirrhosis, end-stage renal disease, and cardiovascular disease [32][33][34][35][36]. The main mechanism of development of fibrosis as a cause of oxidative stress is thought to be in a consequence of oxidative stress which led to increased secretion of TGFb.…”
Section: Biochemical Evaluationmentioning
confidence: 98%